Effects of a R133W β-tropomyosin mutation on regulation of muscle contraction in single human muscle fibres - Ochala, Julien (Blackwell Publishing Ltd, 2007)
A novel R133W β-tropomyosin (β-Tm) mutation, associated with muscle weakness and distal limb deformities, has recently been identified in a woman and her daughter. The muscle weakness was not accompanied by progressive muscle wasting or histopathological abnormalities in tibialis anterior muscle biopsy specimens. The aim of the present study was to explore the mechanisms underlying the impaired muscle function in patients with the β-Tm mutation. Maximum force normalized to fibre cross-sectional area (specific force, SF), maximum velocity of unloaded shortening (V(0)), apparent rate constant of force redevelopment (k(tr)) and force–pCa relationship were evaluated in single chemically skinned muscle fibres from the two patients carrying the β-Tm mutation and from healthy control subjects. Significant differences in regulation of muscle contraction were observed in the type I fibres: a lower SF (P < 0.05) and k(tr) (P < 0.01), and a faster V(0) (P < 0.05). The force–pCa relationship did not differ between patient and control fibres, indicating an unaltered Ca(2+) activation of contractile proteins. Collectively, these results indicate a slower cross-bridge attachment rate and a faster detachment rate caused by the R133W β-Tm mutation. It is suggested that the R133W β-Tm mutation induces alteration in myosin–actin kinetics causing a reduced number of myosin molecules in the strong actin-binding state, resulting in overall muscle weakness in the absence of muscle wasting.